Effects of micro/nano-ozone bubble nutrient solutions on growth promotion and rhizosphere microbial community diversity in soilless cultivated lettuces - Zhao, Qinsong; Dong, Jingjing; Li, Shibiao; Lei, Wenxin; Liu, Ake (Frontiers in Plant Science, 2024)
Due to its high degree of effectiveness as a wide-spectrum disinfectant and potential for the degradation of pollutants and pesticides, ozone has broad application prospects in agricultural production. In this study, micro/nano bubble technology was applied to achieve a saturation state of bubble nutrient solution, including micro-nano oxygen (O2 group) and micro-nano ozone (O3 group) bubble nutrient solutions. The effects of these solutions on lettuce physiological indices as well as changes in the microbial community within the rhizosphere substrate were studied. The application of micro/nano (O2 and O3) bubble nutrient solutions to substrate-cultured lettuces increased the amount of dissolved oxygen in the nutrient solution, promoted the lettuce yield, and increased the net photosynthetic rate, conductance of H2O and intercellular carbon dioxide concentration of lettuces. Diversity analysis of the rhizosphere microbial community revealed that both the abundance and diversity of bacterial and fungal communities in the substrate increased after plant cultivation and decreased following treatment with micro/nanobubble nutrient solutions. RDA results showed that the microbial community in the S group was positively associated with EC, that in the CK and O2 groups exhibited a positive correlation with SC, and that in the O3 group displayed a positive correlation with CAT and POD. Overall, the implementation of micro/nanobubble generation technology in soilless substrates can effectively increase the lettuce growth and yield, and O3 had a more pronounced effect on lettuce yield and quality and the microbial community structure in the substrate than O2. Our study would provide a reference and theoretical basis for developing sustainable and green technology and can be a promising alternative to conventional methods for improving crop yields.